Temporal structure of pedaling cadence variability during road-based cycling - Rouffet, D. M.; Taylor, S.; Stergiou, N. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to analyse the temporal structure of pedalling cadence variability for two groups of subjects (i.e. experienced cyclists and non-experienced cyclists). Pedalling cadence was measured for different parts of the pedalling cycle (i.e. transition and stroke phases) during a road-based ride. Mean ±standard deviation (SD) was calculated and detrended fluctuation analysis (DFA) was applied to the cadence time-series. Smaller standard deviation was calculated in experienced cyclists compared to the non-experienced cyclists during the transition phases (p=0.02) and stroke phases (p=0.03). DFA values were lower in the group of experienced cyclists compared to the group of non experienced cyclists, for both transition phases (p=0.02) and stroke phases (p=0.02). Differences in cadence regulation were observed between experienced and non-experienced cyclists.